Out of Africa: Students' reflections on the personal and professional impact of volunteering. (2nd January 2019) - Power, Alison; Boughen, Adelle; Ames, Charlotte
Abstract : TheNursing and Midwifery Council (2009) states that student midwives should seek opportunities to develop their skills and knowledge base. In the summer of 2018, two student midwives from the University of Northampton independently researched and signed up to a 2-week overseas mission trip to Kenya, with the aim of immersing themselves in a different culture to gain new knowledge and develop transferable skills to embed into their practice in the UK. Charlotte Ames and Adelle Boughen also visited a number of projects around the region supporting girls and young women who have fled their homes to escape injustices such as underage marriage, female genital mutilation (FGM) and domestic abuse. Hearing the young women's stories of bravery, resilience and optimism have had a profound effect on both Charlotte and Adelle, providing them with a new understanding of the term 'with woman' and influencing their future practice.